Poučevanje ruščine kot tujega jezika v slovenskem prostoru - Frank, Meta (Vestnik za tuje jezike, 2015)
The first part of the paper presents a few essential theoretical premises of the methodology of teaching Russian as a foreign language and its brief historical outline. In the second part of the paper the author focuses on the teaching and learning of Russian in Slovenia. The author presents the results of a questionnaire for teachers of Russian, which let her know where Russian language is being taught, which materials the teachers are using, and in which areas they have discovered the biggest problems with learning and mastering the Russian language.
Keywords: Russian; ruščina; tuji jeziki; didactic method; didaktika; jezikovni pouk; napake; Slovenia; Slovenija